2006
DOI: 10.1159/000092188
|View full text |Cite
|
Sign up to set email alerts
|

Varicella-Associated Purpura Fulminans: Chicken Pox Is Not Always Benign

Abstract: Objective: To report a 6-year-old boy with post-chicken pox purpura fulminans (PF). Clinical Presentation and Intervention: A 6-year-old boy presented with purpura of the legs that rapidly progressed to other parts of the limbs and the buttocks. The patient had had chicken pox 10 days prior to presentation. He was afebrile and the chicken pox lesions were dry. He received anti-coagulants, a large volume of fresh frozen plasma, immunoglobulin and steroids. The skin lesions regressed but both hands and parts of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Moreover, a case study on a 6-year-old boy highlighted the association of chickenpox with complications of purpura fulminans. [ 25 ] The child presented with purpura of the legs that rapidly progressed to other parts of the limbs and the buttocks. The authors suggested an early and aggressive treatment of postchickenpox purpura fulminans might reduce the mortality and morbidity associated with this condition.…”
Section: Kuwaitmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a case study on a 6-year-old boy highlighted the association of chickenpox with complications of purpura fulminans. [ 25 ] The child presented with purpura of the legs that rapidly progressed to other parts of the limbs and the buttocks. The authors suggested an early and aggressive treatment of postchickenpox purpura fulminans might reduce the mortality and morbidity associated with this condition.…”
Section: Kuwaitmentioning
confidence: 99%
“…The authors suggested an early and aggressive treatment of postchickenpox purpura fulminans might reduce the mortality and morbidity associated with this condition. [ 25 ] Another study highlighted an outbreak of chickenpox among susceptible staff in an Intensive Care Unit (ICU). [ 26 ] A 4-year-old child diagnosed with chickenpox-associated encephalitis was admitted to the ICU and transferred 12 h later to Infectious Disease Hospital.…”
Section: Kuwaitmentioning
confidence: 99%
“…She responded to prolonged anticoagulant therapy [18]. Another case reported in a 6-year-old boy with purpura fulminans was treated with fresh frozen plasma, anticoagulants, immunoglobulins and steroids [19]. A role of hyperbaric oxygen as an adjunctive therapy in the management of acute thrombotic purpura complicating varicella has been described.…”
Section: Discussionmentioning
confidence: 99%
“…More than 90% of chickenpox cases occur in children < 10 years of age. The disease usually runs a benign course in immunocompetent children although complications such as purpura fulminans necessating skin grafting has been rarely reported 1 . Increased morbidity is seen in adults and in patients who are immunocompromised.…”
Section: Discussionmentioning
confidence: 99%